The influence of attitude and motivation on English performance among religious secondary school students / Nor Hidayati Abdullah - Abdullah, Nor Hidayati (2013)
English language performance of Malaysian students is still below satisfactory level and many studies have been conducted to investigate the factors. Among the factors believed to be influencing the students’ different performance are attitude and motivation. However, most of the studies were undertaken in tertiary education setting and regular secondary school setting. Not much is known about the attitude and motivation of religious secondary school students although poor performance in English is also apparent at this type of school. In an Islamic school setting, the religious secondary school students learn extra religious subjects and Arabic language alongside other academic subjects. Given these differences, there is a possibility that their attitude and motivation in learning English is different from the students in other types of school thus contributing to their performance. Therefore, this study aimed to investigate the influence of attitude and motivation in learning English among religious secondary school students of different level of performance in English. This study employed a primarily quantitative research design and utilized questionnaire together with a semi-structured interview in order to collect data. A total of 199 students from national religious secondary schools in Selangor were involved in this study. Findings revealed that the students have a slightly positive attitude towards learning English. They were moderately motivated and more intrinsically rather than extrinsically motivated in learning English. A significant positive relationship was found between the students’ attitude and motivation in learning English. A significant difference was also found in the attitude of the students of different level of performance in English. However, no significant difference was found in the motivation of the students of different level of performance in English. The micro and macro implications of this study were further highlighted based on the findings.